Application of Earned Value Method for Analysing Cost and Time Performance in the Construction of the Bank Mandiri Flat in Pare-Pare, South Sulawesi - Yuli Sulistiyohadi; Agung Sakti Meldian; Ervina Yuliyanti; Vikar Kurniawan (Asosiasi Dosen Muda Indonesia, 2025)
The Bank Mandiri Pare-Pare Sulawesi flat construction project is scheduled to be completed within 43 weeks with a contract value of Rp. 17,117,245,280. With time and cost constraints, good and thorough control is needed. The purpose of this study is to determine the cost and time performance at the end of the project completion. The method used in this study is the Earned Value method, which combines cost, time, and physical work performance elements. Data obtained from the project include the project schedule, Cost Estimate (RAB), weekly project reports, and actual costs. An analysis of costs, schedules, variances, and performance indices was conducted, highlighting issues that arose during the study. The Project Schedule Performance Index (SPI) at the 39th week review was 1.076, indicating that the project was ahead of schedule. The Project Cost Performance Index (CPI) from week 30 to week 38 showed values below 1, indicating that project expenditures exceeded the budget due to suboptimal progress weighting, as purchased materials were still in transit to the project site and had not yet been counted as progress by the owner. while in week 39, the index began to rise above 1 because progress weighting has become optimal, as the ordered goods have arrived and are now being accounted for in progress.